DYSSS: A Dynamic and Context-Aware Security System for Shared Sensor Networks - Claudio M. de Farias; Luci Pirmez; Luiz F. R. C. Carmo; Davidson Boccardo; Flávia C. Delicato; Igor L. dos Santos; Renato Pinheiro; Rafael O. Costa (International Journal of Distributed Sensor Networks)
In recent years, we have witnessed the emergence of Shared Sensor Networks (SSNs) as a core component of cyber-physical systems for diverse applications. As Wireless Sensor and Actuator Networks (WSANs) design starts shifting from application-specific platforms to shared system infrastructures, a pressing research challenge is security. In scenarios involving unprotected hostile outdoor areas, SSNs are prone to different types of attacks that can compromise reliability, integrity, and availability of the sensor data traffic and sensor lifetime as well. In this work we propose a Dynamic Security System to be applied in the shared sensor network context. Its basic feature is the nodes neighborhood monitoring and collaboration (through the use of the Byzantine algorithm) to identify an attack and enhance security. The proposed security system is dynamic since it is able to manage the availability, integrity, and confidentiality of multiple applications according to the current execution context. It is also resilient, since it is able to support the continuous network operation even in the presence of malicious or faulty nodes. Its resilience is achieved for the capacity of gathering information from several nodes, thus inferring the countermeasures using context information.